PENGARUH METODE PEMBELAJARAN CARD SORT TERHADAP HASIL BELAJAR IPAS KELAS IV SEKOLAH DASAR NEGERI 14 SUNGAI RAYA - Katarena lela; Dessy Setyowati; Riyanti Nurdiana (STKIP Subang, 2025)
This study aims to determine the influence of the Card Sort learning method on student learning outcomes in the IPAS subject of fourth-grade students at SDN 14 Sungai Raya. The research employed a quasi-experimental method with a Nonequivalent Control Group Design. The independent variable in this study is the Card Sort method, while the dependent variable is IPAS learning outcomes. The population consisted of all fourth-grade students, with class IV A as the control group and class IV B as the experimental group. The sampling technique used was non-probability sampling with saturated sampling, totaling 32 and 33 students in each class respectively. The data collection instrument was an essay-type test (pre-test and post-test) developed based on learning achievement indicators. Data were analyzed using prerequisite tests including the normality test (Shapiro-Wilk) and homogeneity test (Levene). Hypothesis testing was conducted using an independent sample t- test. The results showed a significant difference in learning outcomes between the experimental and control classes. This is evidenced by the t-test result of t_calculated (5.405) > t_table (2.000) at a significance level of 0.05. The average post-test score of the experimental class was 78.33, higher than the control class which had an average score of 61.56. Thus, the Card Sort learning method significantly affected the improvement of IPAS learning outcomes among fourth- grade students at SDN 14 Sungai Raya.